2012
DOI: 10.1007/978-3-7091-0956-4_29
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Outcome and Angiographic Vasospasm with the Dynamic Autoregulatory Response After Aneurysmal Subarachnoid Hemorrhage

Abstract: Incidence of angiographic vasospasm and impaired clinical outcome seems to be related to impaired pressure autoregulation following aSAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…This finding is in line with previous reports although different measurement methods were used to quantify the Neurocrit Care degree of CA impairment [1,23,24]. Patients with an unfavorable clinical course showed an early deterioration of ARI-values at day 2 after the initial bleeding with demonstration of a significant negative trend from day 1 until day 8 with significantly lower ARI-values compared to the group with a favorable clinical outcome.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with previous reports although different measurement methods were used to quantify the Neurocrit Care degree of CA impairment [1,23,24]. Patients with an unfavorable clinical course showed an early deterioration of ARI-values at day 2 after the initial bleeding with demonstration of a significant negative trend from day 1 until day 8 with significantly lower ARI-values compared to the group with a favorable clinical outcome.…”
Section: Discussionsupporting
confidence: 91%
“…The ARI has shown good reliability compared to other static indices 22,23 and proofed good reproducibility under physiological and pathophysiological conditions including SAH. 4,7,15,17 There are hints in previous literature that there seems to be an early divergence between dynamic CA courses of patients with VS/delayed infarcts and patients with an unremarkable radiological course. 7 These findings are in line with another recent publication which demonstrated a continuous decline of the ARI values from day 1 till 8 in patients with an unfavorable clinical outcome (mRS ˂3) in contrast to a continuous improvement of the ARI values in patients with a favorable clinical outcome (mRS ࣙ3).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the brain to regulate cerebral blood flow upon blood pressure variations has been described as cerebral pressure autoregulation (CA) . Previous data demonstrated an impairment of CA after aneurysmal subarachnoid hemorrhage (SAH) . Furthermore, it has been demonstrated that occurrence of an early disturbance of autoregulation after SAH is associated with delayed cerebral ischemia (DCI) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have reported that clotted blood and fluid buildup in the subarachnoid space increase ICP, whereas others have reported that blockage of the normal CSF circulation causes enlargement of the ventricles and elevation of ICP [1,3]. Furthermore, recent studies have shown that cerebral vasospasm following aSAH plays an important role in the elevation of ICP [19][20][21]. However, whether the accumulation of subarachnoid hemorrhage causes an increase in ICP has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%